Phytoplankton community structure and water quality assessment in Xuanwu Lake, China - Qu, Senhu; Zhou, Junxiao (Frontiers in Environmental Science, 2024)
Phytoplankton community structure influences the water quality of freshwater lakes and attracts the attention worldwide. The physicochemical parameters including dissolved oxygen (DO), TN, TP, NH4+-N and CODMn and biological index such as Chl.a concentrations were measured in water of different sites of Xuanwu Lake, China in varied seasons. The Trophic level index (TLI) was calculated to evaluate the trophic status of the lake based on critical water quality parameters. The phytoplankton community structure and biomass in the water was also identified and detected. Obvious change of physicochemical parameters and biological index was detected in varied sampling time. The results showed that TN, TP, NH4+-N, CODMn and Chl.a had higher concentrations in June and August with higher temperature. Obtained TLI values from key water quality indicators revealed that Xuanwu Lake exhibited a state of mesotrophic level in December 2021, mild eutrophic level in October and February, and remained in a state of moderate eutrophication during other periods having higher temperature. Chlorophyta exhibited the highest species diversity and accounted for 48.1% of the entire community. Cyanobacteria had higher density compared to other phytoplankton, which suggesting the potential ecological risk in the lake. These findings aligned with the outcomes of the analysis of the phytoplankton community structure, underscoring a certain degree of correlation between the primary water quality indicators and phytoplankton abundance in Xuanwu Lake. That is, higher discharge of contaminant including nutrients potentially dominated the phytoplankton community structure. The continuous monitoring of phytoplankton community and water quality enabled the assessment of its trophic status of urban lake. Appropriate measures such as adjustment of phytoplankton community structure were proposed to mitigate the eutrophication status of lake. The investigation indicated that phytoplankton variation was the important indicator of water quality and supplied direct evidence for the water quality management and ecosystem restoration of urban lakes.